2014
DOI: 10.1590/s0104-66322014000100009
|View full text |Cite
|
Sign up to set email alerts
|

Clay nanoparticles effects on performance and morphology of poly(vinylidene fluoride) membranes

Abstract: -In this study, a comparison between neat poly(vinylidene fluoride) (PVDF) membrane and composite (PVDF-Nanoclay and PVDF-PVP-Nanoclay) membranes is presented. All membranes were synthesized by the phase inversion process, using 18% PVDF, n-methylpyrrolidone as solvent and water as the non-solvent. Demineralized water cross-flow permeation tests were conducted to evaluate the membranes performance. Scanning electron microscopy (SEM) images of the membranes surface and cross-section and water contact angle meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 82 publications
0
9
0
1
Order By: Relevance
“…The dope solutions were prepared by dispersing the nanoclay (when applicable), in the NMP and then dissolving the polymer. The same procedure was previously described in the literature [30][31][32].…”
Section: Ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…The dope solutions were prepared by dispersing the nanoclay (when applicable), in the NMP and then dissolving the polymer. The same procedure was previously described in the literature [30][31][32].…”
Section: Ii)mentioning
confidence: 99%
“…The method used to determine membrane porosity was previously reported (wet/dry weight method) [30,31]. The wet weight was measured after removing the superficial water from membrane sample using two polyester/cellulose wipers and the dry weight was measured using a digital micrometer (Fowler Tools and Instruments; 1.27 to 25,400 µm) after drying the samples.…”
Section: Membrane Porosity and Thicknessmentioning
confidence: 99%
“…A number of other investigations have also been done to modify the PVDF, PPSU, PSf and PES membranes for effective removal and antifouling performance using NOM. Literature reported that bentonite nanoclay was used as modifiers in membrane fabrication [11][12][13][14][15][16][17][18][19][20]. Bentonite clay has smectite group with an arrangement of aluminium-phyllosilicate with tetrahedral silica and octahedral alumina layers.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane modifier like nanoclay (bentonite) has been proved to increase pore size, hydrophilic, antifouling property in polymeric membranes, which has also increased the water permeate flux through the membranes [12]. Naturally available nanoclay is therefore a potential modifier for the polymer for water purification, which provides strong hydrophilicity, good chemical and mechanical strengths with low cost.…”
Section: Introductionmentioning
confidence: 99%
“…The superficial structure, in different magnifications in micrometric scale, do not show the pore structure as it can be seen on other research paper (MIERZWA et al, 2013;MORIHAMA;MIERZWA, 2014). Therefore, the image refinement for pore distribution was not possible to be completed and compared to the membrane calculated porosity.…”
Section: Porosity Thickness and Morphologymentioning
confidence: 82%